RELIGIOUS COUNSELING IN FORMING THE ROLE OF THE COMMUNITY AS A DOOR OPENER FOR GOODNESS AT THE AL-MUJAHIDIN MOSQUE, SUMBERMANJING KULON VILLAGE, MALANG REGENCY - Angger Bimantara (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Religious activities play a strategic role in shaping public awareness and social participation; however, in practice, the level of community involvement in Islamic study circles remains relatively low. This community service program aims to enhance awareness and encourage active community participation as agents of da'wah through religious counseling with the theme “Becoming Openers of the Doors of Goodness.” The method employed is a participatory approach consisting of preparation, implementation of counseling, mentoring, and evaluation stages. The activity was conducted at Al-Mujahidin Mosque in Sumbermanjing Kulon Village, involving approximately 150 participants from diverse backgrounds. The results indicate an increase in participation, understanding, and awareness among participants regarding the importance of individual roles in da'wah. A communicative approach grounded in Islamic values proved effective in transforming participants’ mindsets from passive recipients to active and participatory contributors. Furthermore, this activity strengthened the role of the mosque as a center for religious development and community empowerment based on Islamic values.